Blue space exploring the reasons in participating in open water swimming between male and female swimmers - Aleta, Alejandro Bonifacio A. 2001-; Dimarucut, Alberto L. DSD (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2024)
Open water swimming, or “Blue Space” is a known sport all around the world (Gerrard, 1999). The population of Filipinos participating in open water events is gradually increasing because of organized events promoting this sport (Jung, 2022). There is, however, no local data characterizing the swimmers who engage in open-water swimming. This research aims to analyze the reasons for the growing number of participation in open water events among Filipinos. This research used a descriptive research design, with a survey questionnaire as the research instrument. The survey included 6 binary question statements for their reason in participating in open water swimming, and were asked to elaborate statements answering “Why?” for their “Yes” responses. The study gathered the responses of the 30 local open water swimmers (15 male and 15 female) with the scope of ages 18 to 66 years old.

Using Thematic Analysis, the researcher found that the reasons for participation in open water swimming between male and female participants are thematically similar. The following 6 overall themes that were identified are: Maintain a Healthier Lifestyle, Improvement of Athletic Performance, Building a Positive Community Among Open Water Swimmers, Participating in Variety of Recreational Activities to Stay Physically Active, Breaking the Monotony of Participating in 1 Sport, and Rewards as Motivation. In conclusion based on the overall themes, the emerging reason for the participation in open water swimming of male and female participants is to maintain a healthy and an active lifestyle. In future studies, it is recommended to have more studies that focuses on the open water swimming community on how they can further encourage both genders to be engaged in the sport
Thesis (Bachelor of Sports Science) -- University of the Philippines Diliman
Includes bibliographical references
Keywords: Open water swimming; Swimmers